Synaptic circuits involving gastrin-releasing peptide receptor-expressing neurons in the dorsal horn of the mouse spinal cord - Quillet, Raphaëlle; Gutierrez-Mecinas, Maria; Polgár, Erika; Dickie, Allen C.; Boyle, Kieran A.; Watanabe, Masahiko; Todd, Andrew J. (Frontiers in Molecular Neuroscience, 2023)
The superficial dorsal horn (SDH) of the spinal cord contains a diverse array of neurons. The vast majority of these are interneurons, most of which are glutamatergic. These can be assigned to several populations, one of which is defined by expression of gastrin-releasing peptide receptor (GRPR). The GRPR cells are thought to be “tertiary pruritoceptors,” conveying itch information to lamina I projection neurons of the anterolateral system (ALS). Surprisingly, we recently found that GRPR-expressing neurons belong to a morphological class known as vertical cells, which are believed to transmit nociceptive information to lamina I ALS cells. Little is currently known about synaptic circuits engaged by the GRPR cells. Here we combine viral-mediated expression of PSD95-tagRFP fusion protein with super-resolution microscopy to reveal sources of excitatory input to GRPR cells. We find that they receive a relatively sparse input from peptidergic and non-peptidergic nociceptors in SDH, and a limited input from A- and C-low threshold mechanoreceptors on their ventral dendrites. They receive synapses from several excitatory interneuron populations, including those defined by expression of substance P, neuropeptide FF, cholecystokinin, neurokinin B, and neurotensin. We investigated downstream targets of GRPR cells by chemogenetically exciting them and identifying Fos-positive (activated) cells. In addition to lamina I projection neurons, many ALS cells in lateral lamina V and the lateral spinal nucleus were Fos-positive, suggesting that GRPR-expressing cells target a broader population of projection neurons than was previously recognised. Our findings indicate that GRPR cells receive a diverse synaptic input from various types of primary afferent and excitatory interneuron, and that they can activate ALS cells in both superficial and deep regions of the dorsal horn.